Postoperative Results of Mitral Valve Replacement in Patients with Severe Pulmonary Arterial Hypertension (≥ 50mmhg) - Abdelbaki, Mourad; H., Benalikhoudja; EH, Boudiaf (International Journal of Innovative Research in Medical Science, 2024)
Mitral valve replacement after mitral stenosis is directly related to rheumatic fever, which is very common in our country. The development of PAH is the most frequent evolutionary course of MR. This is a retrospective study of 55 patients with severe PAH. The aim of our study is to demonstrate that severe pulmonary hypertension is not a contraindication to mitral valve replacement, and that long-term results are good.